Microarray and FISH‐based genotype–phenotype analysis of 22 Japanese patients with Wolf–Hirschhorn syndrome. Issue 3 (19th December 2013) - Shimizu, Kenji; Wakui, Keiko; Kosho, Tomoki; Okamoto, Nobuhiko; Mizuno, Seiji; Itomi, Kazuya; Hattori, Shigeto; Nishio, Kimio; Samura, Osamu; Kobayashi, Yoshiyuki; Kako, Yuko; Arai, Takashi; et al.
Abstract Wolf–Hirschhorn syndrome (WHS) is a contiguous gene deletion syndrome of the distal 4p chromosome, characterized by craniofacial features, growth impairment, intellectual disability, and seizures. Although genotype–phenotype correlation studies have previously been published, several important issues remain to be elucidated including seizure severity. We present detailed clinical and molecular‐cytogenetic findings from a microarray and fluorescence in situ hybridization (FISH)‐based genotype–phenotype analysis of 22 Japanese WHS patients, the first large non‐Western series. 4p deletions were terminal in 20 patients and interstitial in two, with deletion sizes ranging from 2.06 to 29.42 Mb. The new Wolf–Hirschhorn syndrome critical region (WHSCR2) was deleted in all cases, and duplication of other chromosomal regions occurred in four. Complex mosaicism was identified in two cases: two different 4p terminal deletions; a simple 4p terminal deletion and an unbalanced translocation with the same 4p breakpoint. Seizures began in infancy in 33% (2/6) of cases with small (<6 Mb) deletions and in 86% (12/14) of cases with larger deletions (>6 Mb). Status epilepticus occurred in 17% (1/6) with small deletions and in 87% (13/15) with larger deletions. Renal hypoplasia or dysplasia and structural ocular anomalies were more prevalent in those with larger deletions. A new susceptible region for seizure occurrence is suggested between 0.76 and 1.3 Mb from 4pter, encompassing CTBP1 and CPLX1, and distal to the previously‐supposed candidate gene LETM1. The usefulness of bromide therapy for seizures and additional clinical features including hypercholesterolemia are also described. © 2013 Wiley Periodicals, Inc.